PENGEMBANGAN MEDIA FLASHCARD PADA MATERI MEMBACA TEKS KELAS IV SEKOLAH DASAR - Septya Kurniasari, Metta; Listyarini, Ikha; Mushafanah, Qoriati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the limited use of reading interest learning media in reading materials, especially Indonesian language compositions. The Feasibility of Flashcard Media for Selecting Grade IV Students of SD Negeri Cangkiran 01 Semarang City Who Are the Most Motivated and Information of SD Negeri Cangkiran 01 in Selecting Grade IV Students of SD Negeri Cangkiran 01 Semarang City Who Are the Most Unused. flashcard media on reading materials for. This type of research can be in the form of development research (research and development/R&D) using ADDIE illustrations and consists of the following stages: testing, designing, developing, using, and evaluating. The population of this study consisted of all students of SD Negeri Cangkiran 01 in the 2024/2025 academic year, and a sample of 25 grade IV students selected using a probability testing strategy, namely simple random testing. Information for this study was obtained through interviews, observations, questionnaires, and documentation. Based on the results of the flashcard media assessment, the media master assessment survey reached a very good standard of 97.3%, the material master assessment reached a very good standard of 93.75%, and the educator assessment survey reached a very good standard of 93.75% of the field data that had been filled in reached a very good standard of 96%. The very good standard and Student Responses Achieved in the Assessment Reached a very good standard of 98.8%. Based on the results of this study, it can be concluded that flashcard media is very useful and important for learning Indonesian in Elementary Schools with teachers equipped with the ability to utilize flashcard media to teach reading texts.